‘Integration-through-Law’: grand theory, revisionist history - Robert Schütze (European Law Open)
How has the European Union been integrated in the past? Legal academics have traditionally pointed to the Court of Justice and to the broader idea of an ‘integration-through-law’. Through its supranational jurisprudence, the Court – not the EU legislature – was thus placed at the centre of the European integration project. The underlying reasons for this dominance of constitutional ‘law’ over legislative ‘politics’ have thereby been the subject of three famous explanations: the ‘equilibrium theory’ (Weiler), the ‘asymmetry theory’ (Scharpf) and the ‘over-constitutionalisation theory’ (Grimm). What are the merits of these grand theories of European integration when measured against the historical record? This article hopes to explore this question in the context of the internal market. Its historical revision begins with an analysis of the respective spheres of normative and decisional supranationalism during and after a foundational period (Sections 2 and 3). This is followed by an examination of the meaning and significance of the Cassis de Dijon judgment in the late 1970s. Through this revolutionary case, a dialectical relationship between the EU Court (‘law’) and the EU legislator (‘politics’) emerges (Section 4) that ultimately leads to the spectacular rise of EU legislation (Section 5) after the SEA. This transformational relationship will provide the critical lens for a historical revaluation of the three grand theories of legal integration (Section 6).